Sejarah Islamisasi Minangkabau - Ridwan Arif (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2020)
Sheikh Burhanuddin is known as a prominent Minangkabau scholar. The Islamization of Minangkabau is commonly associated with him. He is seen as a scholar succeeded in islamizing the Minang community. This study examines the role of Sheikh Burhanuddin in the process Islamization of Minangkabau. It examined the approaches and methods applied by Sheikh Burhanuddin in his efforts to Islamization. This study is a qualitative research, namely library research using the document analysis method. The results indicate that Syekh Burhanuddin was successful in his efforts to Islamize Minangkabau because he used the Sufism approach in his preaching, namely da'wah bi al-hikmah. This approach is implemented in the da'wah method, namely being tolerant of, and adopting local culture (Minangkabau customs and culture). Even further, Sheikh Burhanuddin succeeded in integrating Minangkabau customs with Islamic teachings.